ANALISIS DAMPAK DAN RENCANA MITIGASI PANDEMIK COVID-19 YANG DITINJAU DARI ASPEK OPERASIONAL DAN KEUANGAN DI DIVISI OPERASI 2 PT BRANTAS ABIPRAYA (PERSERO) - Ahmad Sabiq Eko Saputro; Aloysius Harry Mukti; Suryati Veronika (JURNAL ILMIAH BISNIS, PASAR MODAL DAN UMKM, 2022)
The Covid-19 virus, which is designated as a pandemic, continues to grow significantly and sustainably globally. The Covid-19 pandemic that has spread in various countries has had an impact on many sectors, from agriculture, mining, trade to the construction sector. PT Brantas Abipraya (Persero), especially in the Operations Division 2 as a contractor, has anticipated the impact of this pandemic. The purpose of this study was to analyze the impact and mitigation plans of the Covid-19 Pandemic in terms of Operational and Financial aspects that occurred in the Operations Division 2 of PT Brantas Abipraya (Persero). After the financial analysis is carried out, the following can be obtained; The NPV shows a positive number so that this construction business is still feasible. The IRR calculation is found to be 14.53% greater than the interest rate of 10.50%, so this construction business is declared feasible. The payback period is estimated to be in the 12th year. Profitability Index is obtained a value of more than 1, so this construction business is feasible. In the operational aspect, the covid pandemic does not have much effect because government programs still prioritize infrastructure projects that can be carried out by companies but the source of funding from projects comes from the company's own funds and loan funds from banks with SCF or Supply Chain Financing and the value of the cash flow plan is in poor condition. normal.